Linguistic Palette of Ukrainian Scientific Image Forming Potential in World Media - Pliasun , Olga (Current issues of Ukrainian linguistics: theory and practice, 2019)
The paper introduces the most relevant issues of linguistic imageology. In particular, the author focuses on the problem of forming successful image strategies as a set of verbalised image actions aimed at creating a positive image of a country in media. The prospects of the investigated problem are evidenced by numerous scientific explorations conducted in the last decade in leading European and Asian scientific centers. In this study, the scholar explores the works of Spanish linguists (P. Rodriguez, A. Santana Talavera, A. Rodriguez Darias etc.) devoted to the problem of developing the so-called "strategic codes" of successful state image. It is stated that the appeal to subconscious, emotional, mythical and cultural codes is the most effective, which is explained by powerful suggestive potential of modern media. Therefore, in media discourse the author proposes to analyze symbolic association code that is able to relate in the recipient's consciousness a particular symbolic object/precedent phenomenon to the country to which it belongs, particularly, Ukraine. In this context, the author considers linguistic specificity of representation of Ukraine's symbolic figures in state image strategies, primarily, in the image strategy of appealing to values, which is based on axiological principles. The thesis about powerful image forming potential of mathematical (M. Ostrogradsky, G. Voroniy, M. Viazovska) medical, biological (I. Mechnikov, D. Zabolotny, O. Bogomolets, V. Vernadsky, O. Brovarets, M. Rodnina) and other Ukrainian scientific schools is argued. A wide arsenal of linguistic tools used by media to create effective image texts is analyzed. The main image forming markers in such publications are, as a rule, emotionally-evaluative epithetical, metaphorical and peripheral constructions with distinctly positive semantics. Summing up the results, the author concludes that there is a need for professional linguistic analysis of image texts about Ukraine in modern media. In this context, media linguistic imageology, that is able to explain linguistic mechanisms for constructing effective image texts, seems to be one of the most promising research directions of modern neolinguistics.
Keywords: linguistic imageology, image of Ukraine, image strategies, image text, image forming potential.